Wujud Imperatif Wacana Mimbar Jumat Surat Kabar Solopos Edisi Maret-April 2014 : Kajian Pragmatik - Firdaus, Muhammad Zakia; , Prof. Dr. Harun Joko Prayitno, M.Hum (2015)
The purpose of the research are, (1) to determine the embodiment of imperative on "Mimbar Jum'at" discourse in Solopos newspaper, (2) to determine the strategy of imperative speech act on "Mimbar Jum'at" in Solopos newspaper, (3) to implement the imperative form as teaching material in Senior High School (SMA/MA). This research uses qualitative method. The object of the research are the speech of advice (tausyiah) containing the imperative form which is conveyed by ustadz through in Solopos Newspaper. The method of collecting data are by using direct observation and the technique used is note-taking technique. The data are analyzed using the fifth sub-type of match method, it is pragmatic method using dialogue partner decisive instrument. The result of this research are (1) related to imperative form on "Mimbar Jum'at" discourse on Solopos newspaper, it shows 4 forms of imperative. They are general imperative form, request imperative form, allurement imperative form, and oredering imperative form. (2) related to strategy of imperative speech act on Solopos Newspape, it is found 4 strategies. They are literal direct speech act, non-literal direct speech act, literal indirect speech act, and non-literal indirect speech act. (3) related on learning implementation, the imperative form can be implemented in teaching material for grade XI KI.2 KD 3.1, curriculum 2013 of Senior High School (SMA/MA)